Histopathology of the synovial tissue: perspectives for biomarker development in chronic inflammatory arthritides - A. Manzo; S. Bugatti; R. Caporali; C. Montecucco (PAGEPress Publications, 2018)
The histopathological and molecular analysis of the synovial tissue has contributed to fundamental advances in our comprehension of arthritis pathogenesis and of the mechanisms of action of currently available treatments. On the other hand, its exploitation in clinical practice for diagnostic or prognostic purposes as well as for the prediction of treatment response to specific disease-modifying anti-rheumatic drugs is still limited. In this review, we present an overview of recent advances in the field of synovial tissue research with specific reference to the methods for synovial tissue collection, approaches to synovial tissue analysis and current perspectives for the exploitation of synovial tissue-derived biomarkers in chronic inflammatory arthritides.